2017
DOI: 10.1007/s00535-017-1371-9
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis: proton pump inhibitors moderately increase the risk of small intestinal bacterial overgrowth

Abstract: The use of proton pump inhibitors (PPIs) may potentially predispose to the development of small intestinal bacterial overgrowth (SIBO), but this association is controversial due to conflicting results from studies conducted to date. The aim of this meta-analysis was to evaluate the association between the use of PPIs and the risk of SIBO. We systematically searched the online PubMed, Embase, and Cochrane Library databases and Web of Science for relevant articles published up to November 2016. Two researchers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
82
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(90 citation statements)
references
References 53 publications
2
82
0
6
Order By: Relevance
“…Among the 19 eligible studies, 7 found a positive association between PPI intake and increased risk for SIBO, whereas the remaining 12 studies did not show a statistically significant relationship. They concluded that the pooled estimate of the 19 studies demonstrated that PPI use was significantly associated with a moderately increased risk of SIBO (OR 1.71, 95% CI 1.20-2.43) [26]. These findings persisted even on subgroup analysis when studies were examined using different control populations as well as different modalities to diagnose SIBO, such as culture of small bowel aspirates and glucose hydrogen breath tests.…”
Section: Infectious and Inflammatory Diseases Possibly Associated Witmentioning
confidence: 66%
See 2 more Smart Citations
“…Among the 19 eligible studies, 7 found a positive association between PPI intake and increased risk for SIBO, whereas the remaining 12 studies did not show a statistically significant relationship. They concluded that the pooled estimate of the 19 studies demonstrated that PPI use was significantly associated with a moderately increased risk of SIBO (OR 1.71, 95% CI 1.20-2.43) [26]. These findings persisted even on subgroup analysis when studies were examined using different control populations as well as different modalities to diagnose SIBO, such as culture of small bowel aspirates and glucose hydrogen breath tests.…”
Section: Infectious and Inflammatory Diseases Possibly Associated Witmentioning
confidence: 66%
“…In addition, subgroup analysis revealed an association between SIBO and PPI use in studies that used duodenal or jejunal aspirate cultures to diagnose SIBO (OR 7.587, 95% CI 1.805-31.894), but no relationship was found between SIBO and PPI use in studies that used the glucose hydrogen breath test (OR 1.93, 95% CI 0.69-5.42) [25]. In 2017, Su et al [26] reviewed recently published peer-reviewed evidence to evaluate the risk of SIBO among PPI users. Among the 19 eligible studies, 7 found a positive association between PPI intake and increased risk for SIBO, whereas the remaining 12 studies did not show a statistically significant relationship.…”
Section: Infectious and Inflammatory Diseases Possibly Associated Witmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, it is considered that small intestinal bacterial flora is changed to induce small intestinal mucosal injury. Recently, metaanalysis and reviews, including our own, report the statistical relationship between PPI and small intestinal bacterial overgrowth [15][16][17]; and that H. pylori eradication changes intestinal bacterial flora [18]. Thus, there is a high possibility that H. pylori infection induces small intestinal dysbiosis.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial translocation from the gut flora to mesenteric lymph nodes underlies the pathogenesis of SBP . It has been shown that long‐term suppression of gastric acid secretion results in bacterial overgrowth both in the stomach and intestine . However, their studies were not limited to patients with LC.…”
Section: Discussionmentioning
confidence: 99%